Predictors of Out-of-ACO Care in the Medicare Shared Savings Program. Issue 7 (July 2016) - Han, Maria A.; Clarke, Robin; Ettner, Susan L.; Steers, William Neil; Leng, Mei; Mangione, Carol M.
Abstract : Importance: Patients treated outside of their Medicare Shared Savings Program (MSSP) accountable care organization (ACO) likely benefit less from the ACO's integration of care. Consequently, the MSSP's open-network design may preclude ACOs from improving value in care. Objectives: Quantify out-of-ACO care in a single urban ACO and examine associations between patient-level predictors and out-of-ACO expenditures. Research Design: Secondary data analysis using Centers for Medicare and Medicaid ACO Program Claim and Claim Line Feed dataset (dates of service January 1, 2013–December 31, 2013). Two-part modeling was used to examine associations between patient-level predictors and likelihood and level of out-of-ACO expenditures. Subjects: Patients were included if they were prospectively assigned to the MSSP in 2013. Patients were excluded if they declined to share data with the ACO, were not retrospectively confirmed to be in the ACO, or had missing data on covariates. Analytic sample included 11, 922 patients. Measures: Total out-of-ACO expenditures and out-of-ACO expenditures by place of service. Results: Of total expenditures, 32.9% were paid to out-of-ACO providers, and 89.8% of beneficiaries had out-of-ACO expenditures. The presence of almost all medical comorbidities increased out-of-ACO expenditures (800–3000 per comorbidity) across the study population. Racial/ethnic minority groups spent between 1076 and 1422 less outside of the ACO than white patients, which was driven by less out-of-ACO outpatient office expenditures (417–517 less for each racial/ethnic minority group). Conclusions: Out-of-ACO expenditures represented a significant portion of expenditures for the study population. Medically complex patients spent more outside of the ACO and represent an important population to study further. Abstract : Supplemental Digital Content is available in the text.